Improving Forest-Based Livelihoods through Integrated Climate Change Adaptation Planning - Shrestha, Pratima; Gautam, Dev Raj (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Forest-based livelihoods are ruthlessly affected by climate change and other non-climatic stressors. Forests as one of the precious natural assets available in the Chitwan Annapurna area is an appropriate sector to address community and ecosystem vulnerability through adaptation works like plantation, protecting biophysical environment against hazards like landslide, floods, and water scarcity. In Nepal, Community Forest Users Groups with legal entity serves as grassroot organizations in preparation of community based adaptation plan of action (CAPA). Hariyo Ban Program, have facilitated in preparation of community based adaptation plans in remote, vulnerable and marginalized communities of different places of Gandaki river basin. The result shows community perception towards climatic and non climatic stresses and its impacts in forest based livelihoods. Climate change, its variability and extreme events have mystified people’s livelihood and forced them to further suffering. Preparation and implementation of adaptation plans has provided a ray of hope towards addressing adverse impact of climate change. Till date, 142 community adaptation plans are prepared following a methodology on integrated community adaptation planning. Adaptation planning has let community know about the prevailing threats and vulnerabilities in their communities and helped to identify adaptation measures to reduce those threats and vulnerabilities, resulting in improved livelihoods. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10819 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 135-146